Inisiatif Pemuda dalam Penanggulangan Penyalahgunaan Narkoba (Pendampingan Program Sosialisasi KOPAN di Desa Glindah Kedamean Gresik ) - Nanang Abdillah; Pristiwiyanto Pristiwiyanto (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The issue examined in this research is drug abuse among adolescents, which is increasing and becoming a serious problem in Indonesia. The research was conducted in Glindah Kedamean Gresik Village. This research is important because teenagers are the next generation who are vulnerable to the negative influences of drugs, which can damage their physical and mental health as well as disrupt their social relationships and academic achievements. This research aims to raise teenagers' awareness about the dangers of drugs through a socialization program involving an anti-drug youth community (KOPAN – in Indonesia). Problem-solving is carried out through the Participatory Action Research (PAR) method, which involves the active participation of adolescents in the socialization process. These activities include problem identification, development of educational materials, and implementation of socialization. The results of the socialization activities show an increase in teenagers' knowledge about the dangers of drugs. They were enthusiastic and open during the discussion.The impact of this research is the increased awareness and knowledge among teenagers about the risks of drug abuse, as well as the strengthening of social support networks among them. Through collaboration with various parties, it is hoped that these preventive efforts can positively contribute to society and reduce the rate of drug abuse among teenagers